Apakah Praktik Berkelanjutan Meningkatkan Kinerja Keuangan? ESG sebagai Variabel Moderator bagi Profitabilitas dan Nilai Perusahaan - Tedi Rustendi; Fransdito Ali Ilyas (Fakultas Ekonomi Universitas Garut, 2026)
This study examines the impact of profitability on firm value as well as the moderating role of Environmental, Social, and Governance (ESG) in commercial banks listed on the Indonesia Stock Exchange during 2023–2024. Profitability is measured by Return on Assets (ROA), while firm value is proxied by Tobin’s Q. The results show that banks generally exhibit healthy profitability, with KBMI-4 banks outperforming lower KBMI groups. Firm value is mostly categorized as fair, although KBMI-4 banks tend to be overvalued, reflecting strong market confidence. ESG implementation has been adopted but remains at a moderate level overall. Hypothesis testing indicates that profitability affects firm value. Additionally, ESG strengthens this relationship, suggesting that banks integrating ESG into their strategies has an advantage to strengthen long-term performance and stakeholder trust. These results emphasize ESG’s role as a strategic factor in increasing firm value beyond financial performance alone.